2002
DOI: 10.1016/s0735-1097(02)02593-7
|View full text |Cite
|
Sign up to set email alerts
|

Early statin therapy restores endothelial function in children with familial hypercholesterolemia

Abstract: Our data show significant improvement of endothelial dysfunction towards normal levels after short-term simvastatin therapy in children with FH. These results emphasize the relevance of statin therapy in patients with FH at an early stage, when the atherosclerotic process is still reversible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
168
0
13

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(189 citation statements)
references
References 29 publications
5
168
0
13
Order By: Relevance
“…These results are similar to findings reported by other authors (De Jongh et al, 2003;Rodenburg et al, 2004), although significant reductions in LDL cholesterol values were also described in these studies. However, larger, less dense LDL particles appeared after the sterol-enriched diet in this study.…”
Section: Discussionsupporting
confidence: 93%
“…These results are similar to findings reported by other authors (De Jongh et al, 2003;Rodenburg et al, 2004), although significant reductions in LDL cholesterol values were also described in these studies. However, larger, less dense LDL particles appeared after the sterol-enriched diet in this study.…”
Section: Discussionsupporting
confidence: 93%
“…18,20,23,[26][27][28] As can be seen in our results, nine of the adolescents were obese or dyslipidemic. This fact supports the figure of 6.7% (the 10th percentile in our study) endothelium-dependent vascular dilatation as the lower limit of normality in adolescents.…”
Section: Variablessupporting
confidence: 79%
“…However, all of these had patient samples that differed from ours, in particular in terms of age groups. 6,[18][19][20][21][22][23][24][25][26][27][28] While the studies found in the literature employed similar methodology for endothelial function assessment, the employed patient samples which, in addition to including individuals from wider age ranges than the age range of the adolescents in our study, also differ by not having exclusion criteria that could demonstrate that the patient sample was free from metabolic or functional bias.…”
Section: Discussionmentioning
confidence: 99%
“…Interventional trials are warranted to test if this is the case and also to prove that a reduction of hsCRP levels lowers cardiovascular risk. In this context, statin therapy was shown to restore endothelial function in children with familial hypercholesterolemia 56 and has also demonstrated to be safe. 57 In conclusion, our cross-sectional data demonstrate that obese children have elevated blood levels of the inflammation markers hsCRP and hsIL-6 and of E-selectin, a specific endothelial activation marker.…”
Section: Discussionmentioning
confidence: 99%